ANALISIS INVESTASI SEKTOR PERTANIAN DI SULAWESI TENGGARA - Azhar Bafada (Universitas Negeri Medan, 2013)
This study aims to compare theinvestment on agriculture sector in Southeast Sulawesi. Data used are of annually, covering 1990-2009. The analysis is undertaken by using a multiple regression.The result shows that the interest rate of credit, the Gross Regional Domestic Producton agriculturesector simultanaeously to give significant effect to theinvestment on agriculturesector. The value of regression coefficient of the interest rate credit is negative, but the interest rate of credit does not provide a significant to the investment on agriculture sector. Meanwhile, the Gross Regional Domestic Product on agriculture sector has a positive relationship and has a significantto the investment on agriculture sector. The value of regression coefficientby 0,191 indicates that when the GRDP on agriculture sector increase by1 rupiahwill increase investment on agriculture sector by 0,191 rupiah, or when agriculture GRDP increased by 1% then will improve the investment on agriculture sector of 0,97%, or more easily can be defined that if the GRDP of agriculture sector increase, the investment of the agriculture sector will also be increase.